A High‐Resolution Map of Wheat QYr.ucw‐1BL, an Adult Plant Stripe Rust Resistance Locus in the Same Chromosomal Region as Yr29. Issue 1 (1st March 2019) - Cobo, Nicolas; Wanjugi, Humphrey; Lagudah, Evans; Dubcovsky, Jorge
Abstract : The appearance of highly virulent and more aggressive races of Puccinia striiformis f. sp. tritici ( Pst ) during the last two decades has led to stripe rust epidemics worldwide and to the rapid erosion of effective resistance genes. In this study, we mapped an adult‐plant resistance locus from the Argentinean wheat ( Triticum aestivum L.) cultivar Klein Chajá, which is effective against these new Pst races. By using wheat exome capture data and a large population of 2480 segregating plants (4960 gametes), we mapped QYr.ucw‐1BL within a 0.24‐cM region [332 kb in International Wheat Genome Sequencing Consortium (IWGSC) RefSeq version 1.0] on chromosome arm 1BL. This region overlaps with current maps of the adult‐plant Pst resistance gene Yr29, which has remained effective for more than 60 yr. An allelism test failed to find recombination between QYr.ucw‐1BL and Yr29 and yielded similar resistance phenotypes for the two loci. These results, together with similar haplotypes in the candidate region, suggested that QYr.ucw‐1BL and Yr29 might represent the same gene. However, we cannot rule out the possibility of tightly linked but different genes because most of the 13 genes in the candidate region are annotated with functions associated with disease resistance. To evaluate their potential as QYr.ucw‐1BL/Yr29 candidate genes, we characterized their polymorphisms between resistant and susceptible haplotypes. Finally, we used these polymorphisms to develop high‐throughput markers to accelerate the deployment of these Pst resistance loci in wheat breeding programs.